Adaptaciones curriculares para atender las necesidades educativas especiales en estudiantes de educación inicial de la Unidad Educativa Francisco Huerta Rendón - Corrales Naranjo, Nathaly Fernanda (2023)
The research was born as a result of high exclusion and educational inequality in Special Educational Needs and was conducted in the Educational Unit Francisco Huerta Rendón, to improve already tend to students with special educational needs through curricular adaptations in the pedagogical field, application of different methods by teachers or prerequisites needed in each area for students important and effective learning that will help them as living beings to acquire it understanding of their environment, the place in time and space to which they remain adapted and achieve important learning because a curricular habitus is a kind of pedagogical tactic that are aimed primarily at students with special difficulties that is based on the adequacy of a defined level of education in the curriculum that are more available to a student or a defined type of people through the elimination of those who claim resources that they can not get because of their disability. The team that develops a meaningful curricular habit should be the teacher and the academic committee with the professional support of the educational psychologist, because teachers are the delegates to guide students, parents of those students and their own classmates, of course, without forgetting that they need to be taught and appreciated in different ways, so the curricular adaptations of students with special educational needs are also granted.